Perbandingan delik mukah (zina) antara Kitab Undang-Undang Hukum Pidana (KUHP) dan Hukum Pidana Islam - AHMAT, AHMAT ([Yogyakarta] : Universitas Gadjah Mada, 2010)
In this research, authors try to describe comparison of adultery between positive law of Indonesia (Criminal Code) and Islamic Criminal Law. The purpose of this research is to know the difference between adultery according to Article 284 of Law Book Criminal Law (Criminal Code), according of adultery to the draft Penal Code and according adultery to Islamic Criminal Low. So to know a coment views of experts of criminal law and Islamic law on adultery in setting offense renewal of the Penal Code. This research is descriptive analytical and comparative, that is research conducted to compare a variable (object of research), between different subjects or at different times. Explain and describe the data that has been obtained relating to Comparative adultery Between the Book of Law - Law Criminal Law (Penal Code) and then entered the Islamic Criminal Law to find comparison and the difference equation. Elements of adultery regulated by Article 284 of Criminal Code have more moral weaknesses than Islamic Criminal Law. Likewise, punishment sanction to adultery according to the article is light than law application to fornicating criminalization regulated by Islamic Criminal Law. The Islamic Law does not ask whether fornicators have married others or not, those who do sexual intercourse with coercion or based on mutually loving, even sexual intercourse with powerless or unconscious women, and Moslems who do the sexual intercourse without legal marriage remain to be fornication and properly punished.